The effect of nicotine on threat avoidance behaviour in healthy non-smokers - Müller, Madeleine; Korn, Christoph W.; Haaker, Jan (Psychopharmacology, 2025)
Rationale: Developing adaptive strategies for survival relies on distinguishing danger from safety through aversive learning mechanisms. Chronic and acute nicotine exposure have been linked to impaired aversive learning and reduced discrimination between threat and safety. Yet, it is unclear if nicotine also impacts one behavioural consequence of aversive learning, which is the avoidance of threats. Objectives: This preregistered study examines how acute nicotine influences costly avoidance behaviour in non-smokers. Methods: To this end, healthy non-smoking participants (n = 66) received either 1 mg nicotine or a placebo in a double-blind design and underwent an active avoidance task. During acquisition, participants could choose between a safer but longer path to reach their goal or a shorter path (less effort) with a higher chance of receiving an aversive outcome in the form of an electrical stimulus. During uninstructed extinction, both paths no longer contained the risk of an aversive outcome and participants could learn this new safety association by trial and error. Finally, an instructed extinction phase indicated complete safety. Results: Contrary to our pre-registered hypotheses, participants with nicotine intake showed a trendwise reduced avoidance of aversive outcomes, compared to placebo controls. Further analysis revealed however that nicotine did not enhance safety learning during extinction in the nicotine group, as compared to controls. Conclusions: In conclusion, this study strengthens the evidence that nicotine alters learning to identify threat and safety, which is also transferred to avoidance behaviour.